Search for MHC/TCR-Like Systems in Living Organisms - Paganini, Julien; Pontarotti, Pierre (Frontiers in Immunology, 2021)
Highly polymorphic loci evolved many times over the history of species. These polymorphic loci are involved in three types of functions: kind recognition, self-incompatibility and the jawed vertebrate adaptive immune system (AIS). In the first part of this perspective, we reanalyzed and described some cases of polymorphic loci reported in the literature. There is a convergent evolution within each functional category and between functional categories, suggesting that the emergence of these self/nonself recognition loci has occurred multiple times throughout evolutionary history. Most of the highly polymorphic loci are coding for proteins that have a homophilic interaction or heterophilic interaction, between linked loci, leading to self or non-self-recognition. The highly polymorphic MHCs, which are involved in the AIS have a different functional mechanism, as they interact through presented self or non-self-peptides with T cell receptors, whose diversity is generated by somatic recombination. Here we propose a mechanism called "the capacity of recognition competition mechanism" that might contribute to the evolution of MHC polymorphism. We propose that the published cases corresponding to these three biological categories represent a small part of what can be found throughout the tree of life, and that similar mechanisms will be found many times, including the one where polymorphic loci interact with somatically generated loci.